The effects of internationalization, intangible resources and technological change on the transition to a multiproduct company: evidence of the Mexican case (Revista científica Pensamiento y Gestión, 2017)
The objective of this study is to show how the transition from a single- product company to a multiproduct company is generated in a context of internationalization, based on the analysis of the effects of the accumula- tion of tangible resources, intangible resources and technological change. To do this, a panel data regression model was applied with data from the “enterprise survey” generated by the World Bank, in this regression it was applied the xed effects methodology. The results show that the accu- mulation of intangibles, such as human capital, allows a transition to a multiproduct company, but the effect of this accumulation is higher in an internationalized company. In addition, technological change creates incen- tives to not move to a multiproduct company, where this effect is greater in an internationalized company.